PROSES PENGAMBILAN KEPUTUSAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN BENIH JAGUNG HIBRIDA OLEH PETANI DI KECAMATAN ADILUWIH KABUPATEN PRINGSEWU - Jenny Permasih; Sudarma Widjaya; Umi Kalsum (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This study aims to determine the decision process of using the hybrid corn seeds, the relationship between the farmer’s characteristics and the decision of hybrid corn seeds, and the factors that influence farmer’s decision to use hybrid corn seeds.  This research was conducted in two villages, namely Sri Katon village and Waringin Sari Timur village of Adiluwih Subdistrict of Pringsewu Regency.  There are 80 respondents in this study that was chosen by disproportionate stratified random sampling.  The method of analysis in this study is factor analysis using Principal Component Analysis (PCA).  The results showed that the farmers decided of using hybrid corn seeds by the process of introduction needs, information searching, alternative evaluation, purchase decision and post-purchase evaluation. The income and experience of farmers were positively related to their decision of using hybrid corn seeds.  There were three dominant factors that influenced the decision of using hybrid corn seeds. The first component was individual differences which were consisted of farmer’s perceptions of the adequacy of hybrid corn seeds, level in the understanding of hybrid corn seeds, and farmer’s perception on the level of residential proximity of agricultural stall.  The second component was farmer’s perception of the product which was consisted of perception about pests and disease of plant resistance, production, and output.  The third component was farmer’s perception about price, consisted of only one variable namely the price of hybrid corn seeds. Key words: decision making, farmers, hybrid corn seed